SERANGAN HAMA PENGGEREK POLONG PADA ENAM VARIETAS KEDELAI DAN PENGARUHNYA TERHADAP HASIL - Christiawan Poniman; Tri Sunardi; Hesti Pujiwati (BPFP Universitas Bengkulu, 2020)
[POD BORER ATTACK ON SIX SOYBEAN VARIETIES AND THEIR EFFECTS ON YIELD]. This study aims to determine the level of pod borer attack on six soybean varieties and their effects on yields. This research was conducted from December 2017 to March 2018 in the Experimental Field of the Faculty of Agriculture, University of Bengkulu, Kandang Limun Village, Muara Bangkahulu District, Bengkulu City. The experimental design used was a Randomized Complete Block Design (RCBD) with the treatment of six soybean varieties (Demas, Argomulyo, Dega, Ringing, Echo, and Dena I) and was repeated 4 times so that there were 24 experimental units. The results showed that the percentage of pod attack on the Demas, Argomulyo, Ringing, Gema, and Dena I varieties was classified as resistant, while the Dega variety was relatively resistant. Whereas the percentage of seed attack in all soybean varieties tested was classified as resistant. Argomulyo varieties have higher resistance to pod borer attack than other varieties because they produce the highest number of trichomes, and the lowest number of larvae per plant. Argomulyo variety produces the highest number of seed weight per plant, and the highest seed weight per plot. The echo variety produces the highest number of total pods, while the Dega variety produces the highest weight of 100 seeds.